NEW APPROACHES TO TREATMENT OF CHRONIC GINGIVITIS IN CHILDREN - E.A. Yur'eva; A.S. Ivanova; E.E. Yatskevich; G.G. Osokina (Union of pediatricians of Russia, 2007)
The article analyzes efficiency of local immunomodulator manufactured by «npo petrovax farm» for children suffering from chronic gingivitis and multiple caries with congenital and inherited somatic diseases. It evaluated the clinical effect of the medication, the biochemical and immunological parameters of saliva composition of patients who underwent the immunomodulatory therapy. Clinical manifestations of gingivitis disappeared, with the remission during 6 months of the observation. The article shows anti inflammatory, anti oxidant, membrane stabilizing action of the medication. It shows the normalization of cariesogenic products of anaerobic lactate and pyruvate glycolysis, increase of secretory iga (Siga) and lysozyme in the saliva.Key words: children, gingivitis, immunomodulatory therapy.